Novel Method of Speed Control of 3 Phase Induction Motor by Chopper Circuit (International Journal of Innovative Research in Computer Science & Technology, 2022)
Power electronics advancements in recent  years have had a significant influence on the functioning induction machine drives, as well as speed control My  work provides a novel stinger approach for managing the  pitch of a thirty motor. The speed of a three-phase inductor  may be controlled using either a pm dc motor control  technique or directly adding inertia to the stator winding,  as per the documentation. My study is focused on  developing a modern analogue synth controller system  which allows regulating the frequency of a 3 electrical  machine with transcending the limits of present methods. In this technique, a quadcopter circuit will be developed  and when the helicopter's load current grows, the multiple  impulse tire's pressure increased as well. On the  MATLAB/Simulink framework, the same experiment will  be run with turbine load resistance.
Keywords: MATLAB; Power Electronics; Simulink